Cover, Volume 42, Issue 2. Issue 2 (25th January 2021) - Poulter, James A.; Gravett, Molly S. C.; Taylor, Rachel L.; Fujinami, Kaoru; De Zaeytijd, Julie; Bellingham, James; Rehman, Atta Ur; Hayashi, Takaaki; Kondo, Mineo; Rehman, Abdur; Ansar, Muhammad; Donnelly, Dan; et al.
Abstract : The back cover image is based on the Research Article New variants and in silico analyses in GRK1 associated Oguchi disease by James A. Poulter et al., https://doi.org/10.1002/humu.24140 .